2019
DOI: 10.1071/rd18469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold-inducible RNA-binding protein on the proliferation and apoptosis of spermatogenic cells in vitro following heat stress

Abstract: Cold-inducible RNA-binding protein (CIRBP) is reduced by scrotal hyperthermia in cryptorchidism, varicocoele and heat treatment, but there is no direct evidence clarifying the relationship between CIRBP and spermatogenesis. The aim of this study was to investigate the expression of CIRBP in GC2-spd cells (a mouse spermatocyte cell line) before and after heat treatment, and to determine the effects of the downregulation or overexpression of CIRBP on spermatocyte cell proliferation and apoptosis. GC2-spd cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…These findings were consistent with those obtained in the testicular tissue of mice. As in our previous study, 28 the proliferation of GC2 cells was inhibited after heat treatment. We found that the inhibition of miR‐128‐3p expression in GC2 cells increased p‐MAPK14 expression, inhibited cell proliferation, and increased the cell apoptosis rate, consistent with the findings for heat‐treated GC2 cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings were consistent with those obtained in the testicular tissue of mice. As in our previous study, 28 the proliferation of GC2 cells was inhibited after heat treatment. We found that the inhibition of miR‐128‐3p expression in GC2 cells increased p‐MAPK14 expression, inhibited cell proliferation, and increased the cell apoptosis rate, consistent with the findings for heat‐treated GC2 cells.…”
Section: Discussionsupporting
confidence: 80%
“…GC‐2‐spd, the mouse spermatocyte cell line, was obtained from American Type Culture Collection. As described in our previous research, 28 the cells were cultured in Dulbecco's Modified Eagle Medium (Gibco), supplemented with 10% fetal bovine serum and 100 U/mL penicillin and streptomycin, at 37℃ in a humidified atmosphere containing 5% CO2 until an appropriate density was obtained. They were then transferred to a 43℃ incubator for 1 h. Subsequently, the cells were returned to the incubator at 37℃ for further culture.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the genes encoding the cold inducible RNA binding proteins ( cirbpa and cirbpb ) and the high mobility group box proteins ( hmgb1b and hmgb3a ) were regarded as marker genes for cold stress ( Gracey et al, 2004 ; Long et al, 2013 ). CIRBP is a stress-responsive protein has protective effects against tissue injury and cell apoptosis caused by both hyperthermia and hypothermia stressors ( Yu et al, 2018 ; Cheng et al, 2019 ; Liu et al, 2019 ). HMGB1 is the best characterized damage-associated molecular pattern, which is normally inside the cell and is released after cell death or secreted upon severe stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence reveals that Cirbp has been implicated in different physiological and pathological processes, including cell proliferation and differentiation, cell senescence, cell survival and apoptosis, oxidative stress, DNA damage and repair, immune and in ammatory responses, telomere maintenance, circadian rhythm, spermatogenesis, and tumor formation and progression, etc [15][16][17][19][20][21][22][23]. Of note, several lines of evidence has indicated that Cirbp is associated with cell stresses, including heat and cold [24][25][26][27][28][29]. Chronic hypoxia-induced Cirbp hypermethylation attenuated hypothermic cardioprotection via down-regulation of ubiquinone biosynthesis [24].…”
mentioning
confidence: 99%
“…Therapeutic hypothermia protected photoreceptors through activating Cirbp pathway [25]. The down-regulation of Cirbp expression was observed in male germ cells of mice and humans under heat stress condition [26][27][28]. Moreover, in prostate cancer cells, heat treatment upregulated heart shock proteins and down-regulated cold shock proteins [i.e., Cirbp and RNA binding motif protein 3 (RBM3)] [29].…”
mentioning
confidence: 99%